American Spinal Injury Association Impairment Scale Predicts the Need for Tracheostomy After Cervical Spinal Cord Injury. Issue 18 (15th September 2015) - Childs, Benjamin R.; Moore, Timothy A.; Como, John J.; Vallier, Heather A.
<x xml:space="preserve">Abstract</x> Study design. Retrospective review. Objective. The objective of this study was to evaluate the ability of the American Spinal Injury Association (ASIA) Impairment Scale and neurological level of injury to predict the need for mechanical ventilation as well as tracheostomy. Summary of Background Data. High-level cervical spinal cord injuries, high Injury Severity Score, and low Glasgow Coma Scale have been shown to predict tracheostomy. Methods. A total of 383 patients with fractures, dislocations, or ligamentous injury of the cervical spine were included in the study. Charts were reviewed to determine demographics, Injury Severity Score, Glasgow Coma Scale, presence and severity of chest injuries, length of hospital stay, intensive care unit stay, mechanical ventilation time, and mortality. Results. Fifty-nine patients (15.4%) underwent tracheostomy. An ASIA Impairment Scale of A had a specificity of 98.8% and sensitivity of 32.2% for predicting the need for tracheostomy. This yielded a 1.2% false-positive rate. The ASIA Impairment Scale remained the most significant predictor after regression for Injury Severity Score, Glasgow Coma Scale, and Chest Abbreviated Injury Scale. Neurological level of injury was not a significant predictor of tracheostomy. Conclusion. An ASIA Impairment Scale of A at any level of injury is a specific predictor of the need for tracheostomy with a low false-positive rate. Given the relatively low risk of early tracheostomy and the potential benefits, an ASIA Impairment Scale of A would be a sensible early criterion to determine the need for tracheostomy. Level of Evidence: 3